The Bad Guys in Do-you-think-he-saurus? - Blabey, Aaron (New York, NY Scholastic, Inc, 2018)
The Bad Guys find themselves sixty-five million years in the past where they must avoid being eaten by dinosaurs, fix their broken time machine, and get back home before an evil alien destroys the world
English stories
Keywords: Animals -- Fiction; Extraterrestrial beings -- Fiction; Humorous stories; Time travel -- Fiction; Dinosaurs -- Fiction; Dinosaurs -- Juvenile fiction; Superheroes -- Fiction; Aliens (Fictional characters) -- Fiction; Animals; Extraterrestrial beings; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Animals; JUVENILE FICTION -- Humorous Stories; Time travel -- Fiction; Time travel; Graphic novels; Humorous comics; Humorous fiction; Comic books, strips, etc; Graphic novels; Humorous comics; Humorous fiction; Humorous fiction; Humorous fiction